2020
DOI: 10.1177/1687814020940468
|View full text |Cite
|
Sign up to set email alerts
|

Analytical study of floating effects on load sharing characteristics of planetary gearbox for off-road vehicle

Abstract: Uneven load sharing of a planetary gear set is the main cause of preventing the miniaturization and weight reduction of a planetary gearbox. Non-torque loads and carrier pinhole position errors are the main factors that worsen the load-sharing characteristics. However, their effects are seldom analyzed at a system level especially for an off-road vehicle. To make up this gap, some simulation models are proposed to investigate the effects of floating members on the load-sharing characteristics and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Substituting equation (26) into equation (25), the bearing stiffness under odd pressure is obtained:…”
Section: Bearing Stiffness Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting equation (26) into equation (25), the bearing stiffness under odd pressure is obtained:…”
Section: Bearing Stiffness Evaluationmentioning
confidence: 99%
“…Sun et al 24 proposed a signal model of planetary gear set considering the transfer path, and studied the effectiveness and advancement of cyclostationary analysis for fault diagnosis under non-stationary rotational speed excitation. Chung et al 25 optimized the load sharing characteristics of the gear system using only floating members by simulating the dynamic model of the planetary gearbox in the off-road vehicle, so as to reduce the weight and miniaturize the transmission system. Zhang et al 26 declared the tidal periods phenomenon of the fault meshing position of the sun gear inside the planetary gearbox, revealing the new formation mechanism of the fault vibration response and defining the minimum sample length required for such diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, floating components are utilized in a PGS to improve its load sharing performance, as they eliminate the constraint of bearing and enable free movement of components in the radial direction 15 , 16 . However, Chung et al reported the improvement in load sharing performance is limited when non-torque load and carrier PPE are considered 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Wang [18] carried out fault diagnosis research on the planetary gear box containing ring floating, and obtained the system spectrum under floating support. Chung [19] investigates the floating effects on the load sharing behavior of planetary gear set. Yi [20] built a coupled dynamic model to reflect the load sharing behavior in the helical gears-shafts-bearings system, and verified that decreasing transmission error could improve load sharing behavior.…”
Section: Introductionmentioning
confidence: 99%